Total Pancreatectomy With Islet Autotransplantation: Summary of an NIDDK Workshop. Issue 1 (January 2015) - Bellin, Melena D.; Gelrud, Andres; Arreaza-Rubin, Guillermo; Dunn, Ty B.; Humar, Abhinav; Morgan, Katherine A.; Naziruddin, Bashoo; Rastellini, Cristiana; Rickels, Michael R.; Schwarzenberg, Sarah J.; Andersen, Dana K.
Abstract : A workshop sponsored by the National Institute of Diabetes and Digestive and Kidney Diseases focused on research gaps and opportunities in total pancreatectomy with islet autotransplantation (TPIAT) for the management of chronic pancreatitis. The session was held on July 23, 2014 and structured into 5 sessions: (1) patient selection, indications, and timing; (2) technical aspects of TPIAT; (3) improving success of islet autotransplantation; (4) improving outcomes after total pancreatectomy; and (5) registry considerations for TPIAT. The current state of knowledge was reviewed; knowledge gaps and research needs were specifically highlighted. Common themes included the need to identify which patients best benefit from and when to intervene with TPIAT, current limitations of the surgical procedure, diabetes remission and the potential for improvement, opportunities to better address pain remission, GI complications in this population, and unique features of children with chronic pancreatitis considered for TPIAT. The need for a multicenter patient registry that specifically addresses the complexities of chronic pancreatitis and total pancreatectomy outcomes and postsurgical diabetes outcomes was repeatedly emphasized. Abstract : Supplemental Digital Content is Available in the Text.Although utilization of total pancreatectomy with islet autotransplantation in the treatment of chronic pancreatitis has been increasing, many questions remain about who is an appropriate candidate for selection, how to perform the procedure itself, and how to improve outcomes for patients. The National Institute of Diabetes and Digestive and Kidney Diseases convened a workshop in 2014 entitled "Total Pancreatectomy With Islet Auto-Transplantation: Gaps, Needs, and Opportunities." The current state of knowledge was reviewed, and research needs were specifically highlighted.